CORONAPHOBIA AS PSYCHODYNAMICS AND COPING MECHANISMS DURING THE COVID-19 PANDEMIC - Marcelino Giovanni Wirawan (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Introduction – Since first appearing in Wuhan at the end of 2019, the corona virus has caused many losses in various aspects of human life. Starting from the physical-psychological aspect of health and socio-economic. Even now, the new policies adopted by the government also have a huge impact on people's daily habits. One of them is affecting a person's psychology, where the news about COVID-19 has been very developed, causing anxiety and fear among the community. With the many stressors that have emerged in this pandemic era, a person is required to have good coping skills to be able to cope with dangerous stimuli. For someone who has a bad coping skills, he will experience excessive fear and anxiety about the corona virus which is called coronaphobia. Methods – The author makes a review of 20 journals and 2 books discussing definitions, risk factors, psychodynamics, coping mechanisms and management of new phobias in this pandemic era. Results – From several literature reviews, the factors identified in this pandemic era were unforeseen reality, unending uncertainties, need of acquiring new practices and avoidance behavior, loss of faith in health infrastructure, contraction of COVID-19 by head of states, cautionary statements from international bodies, and infodemia. Discuss – Several identified factors factors are assumed to cause interference with routine life, catastrophizing interpretation of benign symptoms, and social amplification of risk which lead to coronaphobia. This requires a person to have a good coping mechanism to adapt to new habits of coexistence with this virus. If the coping mechanism of a person is bad, then the stressor will experience a psychosocial process causing a phobia against COVID-19 which is called coronaphobia.       Conclusion – Coronaphobia is excessive fear and anxiety due to the various effects of the corona virus, be it related to thoughts, information or the illness it causes. This new phobia is caused by the emergence of several risk factors in this pandemic era, which undergo some psychosocial process. Individuals who use maladaptive coping mechanisms are more likely to engage in risky behavior and experience health problems than those with adaptive mechanisms. Therefore, a good coping strategy is needed to avoid the occurrence of psychological problems such as coronaphobia that often arise during this pandemics.     Keywords: coronaphobia, COVID-19, psychodynamic, coping mechanism, fear.